13 pacientes famosos - Fabricant, Noah D (Diana)
Semblanzas médicas sobre los padecimientos de 13 pacientes famosos: F.D. Roosevelt, Hitler, Gandhi, W. Wilson, Proust, D.H. Lawrence, Joyce, F. Scott Fitzgerald, Freud, C. Darrow, Gaugin, G. Gershwin, Caruso.